2017
DOI: 10.1080/01677063.2017.1322079
|View full text |Cite
|
Sign up to set email alerts
|

Novel PNKP mutation in siblings with ataxia-oculomotor apraxia type 4

Abstract: The phenotypic and genetic spectrum of ataxia with oculomotor apraxia (AOA) disorders is rapidly evolving and new technologies such as genetic mapping using whole exome sequencing reveal subtle distinctions among the various subtypes. We report a novel PNKP mutation in two siblings with progressive ataxia, abnormal saccades, sensorimotor neuropathy and dystonia consistent with the AOA type 4 phenotype. Laboratory evaluation revealed hypoalbuminemia, hypercholesterolemia with elevated LDL, elevated IgE levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
11
1
1
Order By: Relevance
“…BMI index was 24.22. LDL increased level (173 mg/dl, nv < 130) confirmed data by Scheiss et al (4), who reported increased LDL and IgE levels in AOA4 patients. The immunoglobulin dosage was not performed.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…BMI index was 24.22. LDL increased level (173 mg/dl, nv < 130) confirmed data by Scheiss et al (4), who reported increased LDL and IgE levels in AOA4 patients. The immunoglobulin dosage was not performed.…”
Section: Resultssupporting
confidence: 89%
“…Mutations in the DNA repair factor polynucleotide kinase phosphatase (PNKP) have been linked to multiple distinct human inherited syndromes. These include (i) microcephaly with seizures (MCSZ, MIM 613402, also known as early infantile epileptic encephalopathy-10), which is characterized by microcephaly, early-onset, intractable seizures, and developmental delay (1), (ii) progressive cerebellar atrophy and polyneuropathy (2), and (iii) ataxia with oculomotor apraxia type 4 (AOA4) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Additional features were cognitive impairment (7/10 patients), increased plasma alpha‐fetoprotein and cholesterol (5/11 patients), and decreased albumin (6/11 patients) (Bras et al, ). In recent years, the availability of next‐generation sequencing or whole exome sequencing in the diagnostic procedure allowed the identification of several patients worldwide with MCSZ (Entezam, Razipour, Talebi, Beiraghi Toosi, & Keramatipour, ; Nair et al, ; Nakashima et al, ) or AOA4 phenotype (Paucar et al, ; Schiess, Zee, Siddiqui, Szolics, & El‐Hattab, ; Scholz et al, ; Tzoulis et al, ) or with symptoms encompassing both conditions (Taniguchi‐Ikeda et al, ). In other cases, the presenting clinical phenotype was characterized by the presence of a motor and sensory axonal polyneuropathy, resembling a form of Charcot–Marie–Tooth disease (Leal et al, ; Pedroso et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…У обоих выявлены атрофия мозжечка при МРТ, полинейропатия смешанного характера при ЭНМГ, гиперхолестеринемия, гипоальбуминемия, нормальный уровень α-фетопротеина. При NGS найдена новая мутация PNKP с.1189-15_119del18 в гомозиготном состоянии [10]. Особенность -внутрисемейные различия возраста начала и интеллекта.…”
unclassified